The effects of teaching special lessons in schools is a field study in schools in Sulaimani - علی, كوێستان (Sulaimani Journal for Humanities, 2019)
The researcher found it necessary to conduct a study on after-school programs which has a more common name “private tutoring” in order to list the impacts of this phenomenon on the applied educational system in particular and the community in general. In order to achieve its objectives, the study adopted nonrandom sampling methodology of selecting the portion of the population to represent the entire population of the study. Consequently, the sampling methodology relied on equal percentage of male and female participation (%50). The age group for the majority was 18, the social status was single, the financial status was good and the majority was city resident. The research found that private tutoring is a widespread phenomenon among Student As a result of conducting this study, many results were pointed out. Above all, the study found that the negative impact of private tutoring on educational system precedes the positive one. Based on the data collected in this study, private tutoring encourages teachers to consider this opportunity as a business transaction, encourages students to escape school classes and become less experienced, and disturbs the development of educational system. It is true that private tutoring can facilitate the process of obtaining higher marks, but only when the student is willing to. Another result of the study found that the financial status of the student eases the communication between the student and the tutor. Finally, the study found that private tutoring has a Significant impact on the mental and psychological state of students.In view of the broader range of this phenomenon to fit many studies and scientific research, the researcher found the need to limit this study to investigate the real motivation behind students contact tutors for private tutoring. Therefore, the study focused on the actual reasons that lead to the spread of this phenomenon at the present time. Indeed, one cannot address such topic without investigating the negative and positive impacts of private tutoring on educational system on one hand and family on the other hand. Perhaps, this will lead us to recognize what the society suffers in the present time from private tutoring. There is no doubt that accepting private tutoring as it is widespread in the Middle East weakens personality of individuals. Since educational system will no longer remain embracing its usual aims, rather, education will become commercial Transactions monopolized by some individuals, this phenomenon, which is limited to the last year of secondary school, is a huge source of discomfort on families that have students receive private tutoring. Furthermore, private tutoring has changed the nature of teacher – student relation which used to be strong over centuries. Instead, the relationship between the two sides has become weak. Additionally, teachers in the present time pay less attention to their duties at school. They less attend classes and not as serious as used to be.